Fabrication of edible chitosan films incorporated with the postbiotic of Pediococcus acidilactici and impact of the edible films on the quality and microbial safety of rainbow trout fillets - Akgol, Muzeyyen; Karatepe, Pinar; Incili, Gokhan Kursad; Tekin, Ali; Oksuztepe, Gulsum; Hayaloglu, Ali Adnan (Elsevier, 2025)
The current study was designed to fabricate and characterize edible films formed by the combination of chitosan and the postbiotic Pediococcus acidilactici and to determine the effects of the produced film on the quality of rainbow trout fillets. In addition, the bioactive compounds in the postbiotic were to be determined. Results showed that the postbiotic contains various bioactive compounds, i.e., volatilomics, organic, free amino, and carboxylic acids. The fabricated films exhibited strong tensile strength (1.89 +/- 0.17 MPa), antibacterial properties against Salmonella Typhimurium, Escherichia coli O157:H7 and Listeria monocytogenes (13.42 to 16.76 mm inhibition zones), and low water vapor permeability (1.55 +/- 0.19 x 10(-10) g mm/m(2) h Pa). In addition, the efficacy of the films was tested on the microbiological and chemical quality parameters of the rainbow trouts at two different storage temperatures (4 and 10 degrees C). The film treatment considerably reduced the numbers of S. Typhimurium, E. coli O157:H7, and L. monocytogenes in comparison to the control fillets (P<0.05). In the rainbow trouts, the number of spoilage microorganisms, including anaerobes, total viable count, psychrotrophs, lactic acid bacteria, and yeast-molds, was found to be lower than the control samples during storage at 4 and 10 degrees C (P<0.05). In addition, the films effectively delayed the oxidation of lipid and proteins when used at an appropriate storage temperature (4 degrees C) (P<0.05). In conclusion, the fabricated films demonstrate the potential to ensure microbial safety by inhibiting foodborne pathogens and delaying the microbiological and chemical spoilage of rainbow trouts.
Keywords: Rainbow trout; chitosan; edible film; Pedioccocus acidilactici; Antimicrobial effect; cell-free supernatant